Acceptability of Philippine English among English Language Teachers - Emma Jenelyn Impas Cainta (k@ta: A Biannual Publication on the Study of Language and Literature, 2025)
Assimilation of new English varieties in English Language Teaching (ELT) is an important topic in contemporary applied linguistics and ELT. Whether or whether English as a Second Language (ESL) instruction in the Philippines should include Philippine English has long been a topic of discussion. Therefore, this study sought to ascertain the degree to which English language teachers found Philippine English (PhE) grammatical and lexical items acceptable. This study employed a quantitative research design using an adopted questionnaire. The findings revealed that the English teachers accepted PhE grammatical and lexical items. Teachers continued to find certain PhE lexical and grammatical issues unacceptable, though. To assist future English teachers in comprehending why Filipino ESL students produce grammatical and lexical elements that deviate from the norm in American English, World Englishes and PhE courses should be revisited within the BSEd English major curriculum.